2006
DOI: 10.1065/espr2006.08.332
|View full text |Cite
|
Sign up to set email alerts
|

U and Th in some brown coals of Serbia and Montenegro and their environmental impact

Abstract: Goal, Scope and Background. The objective of this paper is to determine and compare the concentrations of U and Th in soft to hard brown (lignite to sub-bituminous) coals of Serbia and Montenegro. It also presents comparison of the obtained data on U and Th concentrations with the published data on coals located in some other countries of the world. Almost the whole coal production of Serbia and Montenegro is used as feed coals for combustion in thermal power plants. Methods.Channel samples from open pit and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
(9 reference statements)
3
6
0
4
Order By: Relevance
“…At different places it was already concluded that emissions Al and Cr are coming from the fly ash of these power plants. 27,40,44,32 This is also confirmed by their separate cluster in CA (Fig. 1).…”
Section: Source Appointmentsupporting
confidence: 69%
See 2 more Smart Citations
“…At different places it was already concluded that emissions Al and Cr are coming from the fly ash of these power plants. 27,40,44,32 This is also confirmed by their separate cluster in CA (Fig. 1).…”
Section: Source Appointmentsupporting
confidence: 69%
“…This coal has relatively high concentrations of Mn, which is much higher than Clarke values for brown coals, and this explains the higher Mn content in honeybees sampled at locations near thermal power plants "Kostolac A & B". 44 Ni had statistically higher concentrations at the MS sampling site compared to PV, KO, PABA, PAZV, BGVT and DR sampling sites. Statistically lower concentrations were found at PV in relation to STK, BGPO, DR, BGVT, PAZV and PABA (Table II, Fig.…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 83%
See 1 more Smart Citation
“…A lot of publications dealt with determinations of activity concentrations of natural radionuclides in soil (Spasić Jokić et al 1998;Radosevic et al 2002;Spasić Jokić et al 2002;Bikit et al 2005;Dragović and Onija 2006;Životić D et al 2008), but risk assessment using epidemiological research or with Monte Carlo modeling was never performed.…”
Section: Introductionmentioning
confidence: 98%
“…The literature describes methods based on acid leaching the sample to determine its uranium and thorium activity concentrations by alpha-particle spectrometry [12]. The microwave digestion technique is suitable for determination of trace elements in coals by mass spectrometry [11,13], although the use of HF can cause problems with this technique [14].…”
Section: Introductionmentioning
confidence: 99%